Feedback of patient-reported outcomes to healthcare professionals for comparing health service performance: a scoping review. Issue 11 (23rd November 2020) - Hancock, Shaun L; Ryan, Olivia F; Marion, Violet; Kramer, Sharon; Kelly, Paulette; Breen, Sibilah; Cadilhac, Dominique A
Abstract : Objective: Patient-reported outcomes (PROs) provide self-reported patient assessments of their quality of life, daily functioning, and symptom severity after experiencing an illness and having contact with the health system. Feeding back summarised PROs data, aggregated at the health-service level, to healthcare professionals may inform clinical practice and quality improvement efforts. However, little is known about the best methods for providing these summarised data in a way that is meaningful for this audience. Therefore, the aim of this scoping review was to summarise the emerging approaches to PROs data for 'service-level' feedback to healthcare professionals. Setting: Healthcare professionals receiving PROs data feedback at the health-service level. Data sources: Databases selected for the search were Embase, Ovid Medline, Scopus, Web of Science and targeted web searching. The main search terms included: 'patient-reported outcome measures', 'patient-reported outcomes', 'patient-centred care', 'value-based care', 'quality improvement' and 'feedback'. Studies included were those that were published in English between January 2009 and June 2019. Primary and secondary outcome measures: Data were extracted on the feedback methods of PROs to patients or healthcare providers. A standardised template was used to extract information from included documents and academic publications. Risk of bias was assessed using Joanna Briggs Institute Levels of Evidence for Effectiveness. Results: Overall, 3480 articles were identified after de-duplication. Of these, 19 academic publications and 22 documents from the grey literature were included in the final review. Guiding principles for data display methods and graphical formats were identified. Seven major factors that may influence PRO data interpretation and use by healthcare professionals were also identified. Conclusion: While a single best format or approach to feedback PROs data to healthcare professionals was not identified, numerous guiding principles emerged to inform the field.